Trusted platform for third-party cloud computing online evaluation and analysis technology - Bo ZHAO; Xiang LI; Fei YAN; Liqiang ZHANG; Huanguo ZHANG (网络与信息安全学报)
The service model of cloud computing creates a serious threat to user data security,the trustworthiness of cloud computing through third parties,must be evaluated then the healthy development of the cloud computing industry can be guaranteed.The research of the National High Technology Research and Development Program of China,“trusted platform for third-party cloud computing online evaluation and analysis technology” were summarized.The trusted evaluation model and architecture were described from the cloud platform,the dynamic evaluation technology,the credible evidence collection and the trusted test mechanism,the credibility of the quantitative evaluation method,and the prototype system integrated by tools ,to evaluate the credibility of cloud platform.